HUBUNGAN DUKUNGAN KELUARGA DENGAN KEJADIAN DEPRESI PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT UMUM DAERAH RADEN MATTAHER JAMBI - Desti Herlianda Siregar; Nurfitriani Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2019)
Cancer is a group of diseases caused by single cells that grow abnormally and uncontrollably.Cancer which is the number two cause of death in the world in 2012 was breast cancer (12.90%) after lung cancer (19.70%).In Indonesia, the incidence of breast cancer is highest in the province of Yogyakarta at 40 per 100.000 populations.Jambi province ranks 13th highest out of 34 provinces, with cancer incidence of 1.5 per 1000 population.From 2014 to 2017 there were 1,287 breast cancer patients and had received treatment. Raden Mattaher hospital Jambi is one of the places that served breast cancer treatment,in January to April 2018; there were 39 cases of breast cancer in poly surgery. This study aimed to determine the correlation between family supports with the incidence of depression in breast cancer patients at Raden Mattaher hospital Jambi. This is an analytic descriptive research with population were 39 breast cancer women, it used total sampling technique. This study was conducted at Raden Mattaher hospital Jambi toward 34 breast cancer patients. While 5 patients were respondents in the initial survey. The instruments used a demographic data questionnaire, family support, the incidence of depression; it used univariate and bivariate analysis (fisher exact test). The findings indicated that there is no significant correlation between family supports with the incidence of depression in breast cancer patients with p score were p=0.769. It is concluded that the correlation of good family support did not effect in patients to depression. It is suggested to the next research can study about the correlation of family support with the incidence of depression in breast cancer patients with different method such as qualitative.